2020
DOI: 10.3390/nano10020347
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Roles of Interspace and Controlled Disorder in the Bactericidal Properties of Nanopatterns against Staphylococcus aureus

Abstract: Recent progress in nano-/micro-fabrication techniques has paved the way for the emergence of synthetic bactericidal patterned surfaces that are capable of killing the bacteria via mechanical mechanisms. Different design parameters are known to affect the bactericidal activity of nanopatterns. Evaluating the effects of each parameter, isolated from the others, requires systematic studies. Here, we systematically assessed the effects of the interspacing and disordered arrangement of nanopillars on the bactericid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 46 publications
0
50
0
Order By: Relevance
“…In line with this, another study identified that the killing efficiency of nanopillars (h: 190 nm, d: 80 nm) against Staphylococcus aureus bacteria increased by decreasing the interspace between the pillars [141]. Intriguingly, identical disordered nanopillars did not show a similar outcome [141]. Furthermore, multi-directional nanospikes (d: 120 nm, h; 300 nm, s: 200-400 nm) showed biocidal activity against both Staphylococcus aureus and Pseudomonas aeruginosa bacteria [142].…”
Section: Nature-inspired Architectures To Guide Cell Behaviourmentioning
confidence: 81%
See 3 more Smart Citations
“…In line with this, another study identified that the killing efficiency of nanopillars (h: 190 nm, d: 80 nm) against Staphylococcus aureus bacteria increased by decreasing the interspace between the pillars [141]. Intriguingly, identical disordered nanopillars did not show a similar outcome [141]. Furthermore, multi-directional nanospikes (d: 120 nm, h; 300 nm, s: 200-400 nm) showed biocidal activity against both Staphylococcus aureus and Pseudomonas aeruginosa bacteria [142].…”
Section: Nature-inspired Architectures To Guide Cell Behaviourmentioning
confidence: 81%
“…It was concluded that bacterial attachment becomes more disordered as spacing between pillars decreases, with increasing high-aspect-ratio being key in preventing bacterial attachment. In line with this, another study identified that the killing efficiency of nanopillars (h: 190 nm, d: 80 nm) against Staphylococcus aureus bacteria increased by decreasing the interspace between the pillars [141]. Intriguingly, identical disordered nanopillars did not show a similar outcome [141].…”
Section: Nature-inspired Architectures To Guide Cell Behaviourmentioning
confidence: 84%
See 2 more Smart Citations
“…Evaluating the effects of each parameter, isolated from the others, requires systematic studies. A recent article has evaluated the influence of the interspacing and disordered arrangement of nanopillars on the bactericide properties of nanopatterned surfaces [ 35 ]. Electron beam induced deposition (EBID) was used to manufacture the nanopatterns with accurately controlled dimensions as well as disordered versions of them.…”
mentioning
confidence: 99%